The (non)limits of the regular layout: the empty space in the gridding of Hedra - Borges, Caetano Galindo (9 Arte (São Paulo), 2023)
It explores the empty spaces on the comics page based on its materiality. However, it is not about gutters. The objective is to understand how these spaces influence visual and narrative dynamics of the page. The starting point here is the concept of regular layout (Groensteen, 2015, p.103) and how these empty spaces can influence it. To this end, combining visual theory and arthrology, a case study will be made using the work Hedra by Jesse Lonergan. The objective is to show how the omission of frames creating empty spaces allows manipulating the composition of the page without completely breaking with the fixed structure that the regular layout proposes. It is understood that there is a dynamic of fulfilled and subverted expectations where empty space becomes a rhetorical and poetic element.